PREVENTION AND TREATMENT OF THROMBOSIS AND THROMBOEMBOLIAS WITH ORAL ANTICOAGULANTS - G. V. Arkadyeva (Российский кардиологический журнал, 2003)
Prevention and treatment of thrombosis and thromboembolias with oral anticoagulants.